The use of phosphomannose isomerase selection system for Agrobacterium-mediated transformation of tobacco and flax aimed for phytoremediation - Hilgert, Jitka; Sura-De Jong, Martina; Fišer, Jiří; Tupá, Kateřina; Vrbová, Miroslava; Griga, Miroslav; Macek, Tomáš; Žiarovská, Jana (Journal of environmental science and health. Part B, Pesticides, food contaminants, and agricultural wastes, 2017)
A plant selection system based on the phosphomannose isomerase gene (pmi) as a selectable marker is often used to avoid selection using antibiotic resistance. Nevertheless, pmi gene is endogenous in several plant species and therefore difficult to use in such cases. Here we evaluated and compared Agrobacterium-mediated transformation of Linum usitatissimum breeding line AGT-952 (without endogenous pmi gene) and Nicotiana tabacum var. WSC-38 (with endogenous pmi gene). Transformation was evaluated for vectors bearing transgenes that have the potential to be involved in improved phytoremediation of contaminated environment. Tobacco regenerants selection resulted in 6.8% transformation efficiency when using a medium supplemented with 30 g/L mannose with stepwise decrease of the sucrose concentration. Similar transformation efficiency (5.3%) was achieved in transformation of flax. Relatively low selection efficiency was achieved (12.5% and 34.8%, respectively). The final detection of efficient pmi selection was conducted using PCR and the non-endogenous genes; pmi transgene for flax and todC2 transgene for tobacco plants.
Keywords: geneticky modifikované rostliny; biodegradace; Plants, Genetically Modified; selekce (genetika); Transformation, Bacterial; Nicotiana; Agrobacterium; Mannose; mannosa-6-fosfátisomerasa; Culture Media; Selection, Genetic; kultivační média; len; Mannose-6-Phosphate Isomerase; bakteriální transformace; Flax; Biodegradation, Environmental; mannosa; tabák